Collisional emplacement history of the Naga-Andaman ophiolites and the position of the eastern Indian suture - Acharyya, Subhrangsu K (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 p.87-8